Investigating the association of proton pump inhibitors with chronic kidney disease and its impact on clinical practice and future research: a review - Ejaz Cheema (Taylor & Francis Group, 2019)
Background Proton pump inhibitors (PPIs) are used worldwide for the treatment of gastroesophageal reflux disease (GERD) and peptic ulcer disease (PUD). Although considered to be widely safe, PPIs have been associated with the potential risk of adverse effects such as infections including pneumonia and Clostridium difficile, malabsorption of vitamins and minerals, dementia and more recently with chronic kidney disease (CKD). Evidence including large cohort studies suggests that there is a greater risk of developing CKD in chronic users of PPIs. However, the association of CKD with PPI use reported in these studies is weak and does not establish a clear causality. This review aims to further investigate the association of CKD with PPI use by including studies with various study designs. Methods A literature search of published articles with no start date restrictions was undertaken in May 2018 in three electronic databases (PubMed, ScienceDirect, Google Scholar). Search terms included 'Proton Pump Inhibitors', 'chronic kidney disease', and 'association'. Both observational and randomised controlled trials (RCTs) investigating the association of CKD with PPI use were eligible for inclusion. Results Ten observational studies with 1,005,899 patients contributed to the review. No experimental study was available for inclusion in the review. Of the included studies, six used a retrospective study design, while the rest were prospective (two) or a case-controlled studies (two). A large prospective cohort study with 144,032 patients conducted in the USA reported that PPI use compared to no PPI use was associated with an increased risk of CKD Hazard ratio [HR] 1.28; 95% Confidence Interval [CI] 1.22-1.34. However, the observational study design of this study together with other studies included in the review suggests that the strength of evidence associating PPI use with CKD is weak and does not establish true causality. Conclusions The current evidence related to the potential association of CKD with PPI use remains inconclusive in establishing true causality. Further prospective studies including randomised controlled trials and cohort studies would be required to confirm the findings reported in this review and to draw any conclusions.